Increased risk of vascular complications in patients with type 2 diabetes and fatty liver disease - Weixia Sun; Dechen Liu; Ting Yang; Ziwei Zhou; Dan Li; Zhuoxiao Zhao; Xuan Zhang; Liyun Wang; Ling Li (BMC Endocrine Disorders)
Abstract Background The prevalence of steatotic liver disease (SLD) in patients with type 2 diabetes (T2DM) exceeds 50%. This study aimed to investigate the clinical characteristics of SLD and liver fibrosis in Chinese patients with T2DM. Methods Inpatients from 2021 to 2023 were included in the study. Fatty liver index (FLI) and fibrosis-4 (FIB-4) were calculated to assess hepatic steatosis and fibrosis respectively. Statistical analysis was completed by SPSS v25 and GraphPad Prism v8.0.1. Results Of the 1466 participants, about one-third of the patients in T2DM-SLD group were diagnosed with liver fibrosis (LF), and the percentage of patients over 50 years old was 85.9%. Patients with SLD had higher levels of BMI, blood pressure, liver enzymes, fasting blood glucose (FBG), HbA1c, C-peptide, total cholesterol (TC) and triglyceride (TG) (P<0.05 for all). Patients with liver fibrosis had lower TC, TG, hemoglobin (Hb), erythrocyte count (RBC), leukocyte count (WBC) and platelet (PLT) levels (P<0.05 for all). Compared with simple T2DM and SLD-NLF (non-liver fibrosis) groups, for patients over 50 years old, the prevalence of coronary heart disease, stroke, tumor, and diabetic nephropathy was higher in patients with liver fibrosis. Liver fibrosis might be the risk factor of arterial stiffness, stroke, coronary heart disease and numbness based on multivariable logistic regression analysis. Conclusion Hepatic steatosis and fibrosis were common in patients with T2DM. Liver fibrosis was relevant to many macrovascular and microvascular diabetic complications.